Are adverse effects of antiepileptic drugs different in symptomatic partial and idiopathic generalized epilepsies? the Portuguese-Brazilian validation of the Liverpool Adverse Events Profile - Martins, Heloise Helena [UNIFESP] (2016)
Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES)